-7(6b-7)=-5b+12

Simple and best practice solution for -7(6b-7)=-5b+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(6b-7)=-5b+12 equation:


Simplifying
-7(6b + -7) = -5b + 12

Reorder the terms:
-7(-7 + 6b) = -5b + 12
(-7 * -7 + 6b * -7) = -5b + 12
(49 + -42b) = -5b + 12

Reorder the terms:
49 + -42b = 12 + -5b

Solving
49 + -42b = 12 + -5b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '5b' to each side of the equation.
49 + -42b + 5b = 12 + -5b + 5b

Combine like terms: -42b + 5b = -37b
49 + -37b = 12 + -5b + 5b

Combine like terms: -5b + 5b = 0
49 + -37b = 12 + 0
49 + -37b = 12

Add '-49' to each side of the equation.
49 + -49 + -37b = 12 + -49

Combine like terms: 49 + -49 = 0
0 + -37b = 12 + -49
-37b = 12 + -49

Combine like terms: 12 + -49 = -37
-37b = -37

Divide each side by '-37'.
b = 1

Simplifying
b = 1

See similar equations:

| 3x(-32)=(-7)+28 | | 4(11-2x)= | | 8x+8=(4x)8 | | 3a=-4b-16 | | 6(8x-7)-8(-4x-1)=-34 | | 6a+5am=-11 | | Q+14=8(q+1) | | 12x+7=-10x-4 | | x-.36=1.3 | | 3m^2+6m+9=6 | | x+15=135 | | 10x+35+1x^2+40=30x | | =p+5+9 | | 8x-64=108 | | x+11=5x-5 | | 2*[3+2*(9-5)]= | | 8x+108=64 | | 6x+18-2x-6= | | -32=-3(p+8)-8(1+8p) | | 5x=9.5 | | 8x=164 | | -(y+4)= | | 8x+64=108 | | 4x+2(x-4)=34 | | -23=-9(10+x) | | -8(n-5)=-2(4n+11) | | 66-6x=42 | | 0.183x+0.09(15000-x)=2559 | | 6x+18-2x= | | 8t-8=120 | | x-3+74+41=180 | | 2.5n=45 |

Equations solver categories